Corrections to “Some T-Spherical Hesitant Fuzzy Shapley Bonferroni Mean Operators and Their Applications” - Yongfeng Pang; Wei Yang (IEEE Access)
In the above article [1], reference 18 was retracted. As the work in this reference is no longer reliable, we are removing it from the reference list. A substitute for the retracted reference is not necessary.